Development of advanced automated test equipment for digital system by using FPGA - Adharul Muttaqin; Zainul Abidin; Raden Arief Setyawan; Itsna Az Zahra (Institute of Advanced Engineering and Science, 2019)
One of the fundamental devices in electronics, Integrated Circuit (IC), is usually applied in more complex devices. Before the IC is used, it has to pass some tests to guarantee that its function is in accordance with the specifications. Automated Test Equipment (ATE) is used to test many electronics devices, including ICs. Nowadays, with the rapid advance in electronics technology, the industry will need more advanced ATE to fulfill customers demand. One of the applicative solutions is improvement and integration of a standalone module in commercial ATE owned by the company. ASL 1000 Test System is one of the ATE that is still widely used in industry. ASL 1000 has one limitation in one of its module, Digital Driver and Detector (DDD). The limitation is how much vector pattern that can be saved in the memory. Based on the observation in DDD instrument, a standalone module that has similar specifications as DDD can be designed using Field Programmable Gate Array (FPGA) as its base component. In the standalone module plan, supporting circuits are used, these are interface circuit between FPGA and PC using RS-232 and ASIC as ATE drivers or comparators to connect FPGA and device under test (DUT). The result of the study shows that the designed module can receive and send 8-bit data at 19.200 baud rate. It can write and read 16-bit data from and to SDR SDRAM within 90 ns and 80 ns for one cycle. It can control DAC type AD5308 in standalone operation and DAC type AD5676 in daisy chain operation to generate specific voltage in specific channel. In behavioral simulation, main controller module has already worked in accordance with the desired specifications.